Expectant Management of a Twin Pregnancy with Complete Hydatidiform Mole and Coexistent Normal Fetus. (7th October 2019) - Johnson, Colin; Davitt, Caroline; Harrison, Rachel; Cruz, Meredith
Abstract : Twin pregnancies complicated by complete hydatidiform mole coexisting with a viable fetus are rare and may result in significant complications. We describe the expectant management and our surgical approach in a 27-year-old Rh-negative woman presenting with recurrent episodes of vaginal bleeding and a twin pregnancy consisting of a molar pregnancy coexisting with a normal fetus. Inpatient management was undertaken with close maternal and fetal monitoring until cesarean delivery of a healthy female infant and histopathologically confirmed complete hydatidiform molar pregnancy (karyotype 46XX) at 34 weeks with no evidence of malignancy.